1988
DOI: 10.2170/jjphysiol.38.643
|View full text |Cite
|
Sign up to set email alerts
|

Peptidergic inhibition of cholinergic transmission in bullfrog sympathetic ganglia.

Abstract: Intracellular and voltage-clamp recordings were made from sympathetic B neurons to investigate an interaction between peptidergic and cholinergic responses in bullfrog sympathetic ganglia. Stimulations of both 3rd-5th (0.2 Hz) and 8th (30 Hz) spinal nerves evoked the fast excitatory postsynaptic potential (EPSP) superimposed with the late slow EPSP at the same sympathetic neuron. The amplitude of fast EPSPs was decreased during the course of the late slow EPSP in a majority of sympathetic neurons. The mean dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, it has also been shown that the fast EPSP of B neurons is depressed during the late slow EPSP by decrease of ACh release from preganglionic endings (Hasuo and Akasu, 1988). Ionic mechanisms of receptor activation in amphibian ganglia have been extensively reviewed by Smith (1994).…”
Section: Principal Neurons and Their Synapsesmentioning
confidence: 99%
“…However, it has also been shown that the fast EPSP of B neurons is depressed during the late slow EPSP by decrease of ACh release from preganglionic endings (Hasuo and Akasu, 1988). Ionic mechanisms of receptor activation in amphibian ganglia have been extensively reviewed by Smith (1994).…”
Section: Principal Neurons and Their Synapsesmentioning
confidence: 99%
“…whereas the slow IPSPs are not able to block it, but only to prevent repetitive discharge in C neurons (Dodd and Horn, 1983b). However, it has also been shown that the fast EPSP of B neurons is depressed during the late slow EPSP by decrease of ACh release from preganglionic endings (Hasuo and Akasu, 1988). Ionic mechanisms of receptor activation in amphibian ganglia have been extensively reviewed by Smith (1994).…”
Section: Figsmentioning
confidence: 99%